2013
DOI: 10.1016/j.ophtha.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Functional Improvement after One- and Two-Eye Cataract Surgery in the Salisbury Eye Evaluation

Abstract: Purpose To determine the impact cataract and cataract surgery have on clinical measurements of vision, reading speed, objective mobility performance, and subjective visual functioning. Design Prospective, population-based study Participants 1,739 Salisbury Eye Evaluation (SEE) participants without previous cataract surgery with bilateral baseline best corrected visual acuity (BCVA) of logarithm of the Minimum Angle of Resolution (logMAR) ≤ 0.3 (20/40 or better) or cataract surgery between round 1 and 2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Cataract surgery is recognized to both reduce the risk of falls, a serious injury in older adults, [22][23][24][25][26][27][28][29] and improve driving safety 30,31 probably due to the remarkable improvement in visual recognition after surgery. Therefore, gait speed is a useful health index to evaluate the systemic effects of cataract surgery, 32 and we previously developed an estimation of remaining years of life based on gait speed in cataract patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cataract surgery is recognized to both reduce the risk of falls, a serious injury in older adults, [22][23][24][25][26][27][28][29] and improve driving safety 30,31 probably due to the remarkable improvement in visual recognition after surgery. Therefore, gait speed is a useful health index to evaluate the systemic effects of cataract surgery, 32 and we previously developed an estimation of remaining years of life based on gait speed in cataract patients.…”
Section: Introductionmentioning
confidence: 99%
“…Also previous studies have found a link between depressive symptoms and level of visual acuity (9)(10)(11)(12)14,15,24,(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 81%
“…The level of visual acuity of the non-operated eye is an important element in the level of depressive symptoms (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Its importance stems from the fact that 30-60% of surgical interventions involve the second eye. 8,118 The last factor to be taken into account in this subject is the level of surgical activity developed by a given health service and the social or political tolerance to the existence of waiting lists, 20 which brings up a number of significant issues such as the repercussions derived from remaining in waiting lists for long periods of time 119 as well as the prioritization of patients for accessing said surgery. 116,117 It is estimated that in the future the number of second eye surgeries would increase significantly, which in turn would increase the CSR.…”
Section: Variability and Health Planningmentioning
confidence: 99%